The Effect of Policy and Technological Innovations of Land Tenure on Small Landholders’ Credit-Worthiness: Evidence from Ethiopia - Shewakena Aytenfisu Abab; Feyera Senbeta; Tamirat Tefera Negash (Land, 2023)
Since the early 2000s, Ethiopia has been implementing one of the largest land certification and digitalization programs in Africa, underpinned by technological and policy innovations. The reform indicates a promising avenue for increasing the collateralization of land use rights for smallholder households who have been credit constrained. However, there is scant evidence to what extent these reforms have influenced access to credit. To help generate new insights and fill this gap, the study employed administrative data generated from 11 districts’ digital land registers, survey data from 2296 households in 19 districts, key informant interviews, and policy and legal framework review. Descriptive and inferential statistics complemented by qualitative explanations are employed to analyze the results of the study. The results revealed that accessibility of information from the digital rural land registers increased the credit-worthiness of small landholders and reduced transaction costs and risks. The reform related to collateralization of land use rights also incentivizes financial institutions to establish new loan products for small landholders. The study concludes that while the two-stage land certification programs allow smallholders to possess documented land rights, their credit-worthiness may likely remain negligible without further technological and policy innovations. This implies two policy issues: the need to reform secured transaction laws and digitalizing registries for higher land rights trade ability.